" Diseño de un plan para la creación de un centro de actividades diurnas para el adulto mayor en el sector este del Gran Área Metropolitana" - Ivankovich-Guillén, Ana Lucía; Jiménez-Valverde, Denia; Morales-Martínez, Gabriela (Instituto Tecnológico de Costa Rica, 2011)
In most countries, elderly population has grown up and Costa Rica is no exception to this phenomenon. As a consequence, in the last years there has been a significantly increase on demand for services and care of this segment of the population. Among the services offered in our country to these people, there are Day Care Centers, which are an option for providing care, socialization and recreation. However, these centers are considered as welfare institutions and then, they are focused to low income people, not being an attractive option for the mid-high and high income level individuals. The above described situation generates a business opportunity, to satisfy the needs of this segment of the elderly population. Our initial research showed that nationwide, there is only one Day Center profit oriented, which is located West bound of the Greater Metropolitan Area (GMA). For the reasons above explained, our group developed this project, which general objective was to design the Plan for the setting up of a Day Care Center for the elderly population, oriented to the mid-high and high income segments of the East bound of the GMA. Specific objectives were addressed to:  Develop a feasibility study, including analysis of market; technical; legal environmental and financial aspects of the project.  Prepare management plans (approach, timing, costs, quality, human resources, communications, risks and acquisitions), that allow to set the proposed Plan up. This project pretends to be one of descriptive kind, since its purpose is to describe a situation or event. For that, primary and secondary sources were used to get the required information. Among the conclusions we got, it is important to highlight that the proposed Plan gets together a series of support processes which are a very good guide and orientation for those who want to establish a Day Care Center for the elderly population. Then, this project can be used as a tool for the right planning and should be complemented with a proper planning and management in the other stages of the project, in order to ensure its success. Finally, we do recommend that interested investors proceed to update information regarding legislation, technical requirements, costs timing and risk estimation, at the time they start analyzing to develop a Day Care Center, as the one described here.
Proyecto de Graduación (Maestría en Gerencia de Proyectos) Instituto Tecnológico de Costa Rica. Escuela de Administración de Empresas. Escuela de Ingeniería en Computación. Escuela de Ingeniería en Construcción, 2011
Keywords: Factibilidad; Mercado; Recurso humano; Costos; Inversión estratégica; Gastos